2010
DOI: 10.1556/avet.58.2010.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Application of a solid-phase fluorescence immunoassay to determine amoxicillin residues in fish tissue

Abstract: The present study demonstrates an application of Parallux (a solid-phase fluorescence immunoassay) for amoxicillin analysis in fish tissue. Amoxicillin at the recommended therapeutic dose (400 mg/kg body weight) was orally administered to three groups of 25 olive flounder ( Paralichthys olivaceus ), 25 rockfish ( Sebastes schlegeli ) and 25 red sea bream ( Pagrus major ) for 7 consecutive days. Amoxicillin was detected in the muscle of fish treated by the 3rd day of the withdrawal period. The recovery rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Moreover, Carballeira et al (2012) studied the toxicity of AM on fish and found similar sensitivities to all substances tested. In addition, Park et al (2010) detected AM in fish tissue after the 3 rd day of spiking in water. Liu et al (2012) studied the toxicity AM and microcystins against algae and found that Spiramycin is more toxic to M. aeruginosa than AM according to their EC 50 values.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, Carballeira et al (2012) studied the toxicity of AM on fish and found similar sensitivities to all substances tested. In addition, Park et al (2010) detected AM in fish tissue after the 3 rd day of spiking in water. Liu et al (2012) studied the toxicity AM and microcystins against algae and found that Spiramycin is more toxic to M. aeruginosa than AM according to their EC 50 values.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, most countries have turned to cultured Clarias species for their high reproductive capacity under natural and controlled conditions, high growth rate, tolerance of bad water conditions and high nutritional value (Ikpi & Offem, ; Khan & Abidi, ; Maneechot et al, ). Several trials using herbal and alternative medicine in fish culture (Hoseinifar et al, ) have been performed to overcome the side effects of using antibiotics for controlling different diseases that cause severe issues in humans, especially drug resistance and antibiotic residues (Chafer‐Pericas et al, ; Obaidat, Salman, & Lafi, ; Park, Jung, & Lee, ). Probiotic (Mehdinejad, Imanpour, & Jafari, ; Meidong et al, ), prebiotic (Bai, Tsuruta, & Nishino, ; Forsatkar, Nematollahi, Rafiee, Farahmand, & Lawrence, ) and even immune‐modulating agents have been used (Fuchs, Schmidt, Slater, Buck, & Steinhagen, ; Valenzuela, Rodriguez, Modak, & Imarai, ).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to these two approaches, rapid tests specific to β-lactam antibiotics, for example, Charm test and Parallux, are often adopted for fast screening. 17,2628 Furthermore, there has been a growing trend in developing innovative biosensors for simple, speedy, reliable, and efficient screening of antibiotic residues in food and clinical specimens. 19,2932…”
Section: Introductionmentioning
confidence: 99%